The Prospects of Non-EEG Seizure Detection Devices in Dogs - Bongers, Jos; Gutierrez-Quintana, Rodrigo; Stalin, Catherine Elizabeth (Frontiers in Veterinary Science, 2022)
The unpredictable nature of seizures is challenging for caregivers of epileptic dogs, which calls the need for other management strategies such as seizure sensor devices. Non-electroencephalographic (non-EEG) devices have been described in epileptic humans, such as heart rate variability (HRV), accelerometry (ACM), electrodermal activity (EDA), and electromyography (EMG). Their sensitivity and false detection rate vary, however direct comparison of studies is nearly impossible, as there are many differences in study design and standards for testing. Although seizure detection via wearable intracranial EEG recordings is associated with a higher sensitivity, there is robust evidence for reliable detection of generalised tonic-clonic seizures (GTCS) using non-EEG devices. A way to improve sensitivity and decrease false-positive alarms is to combine the different parameters thereby profiting from the strengths of each one. Given the challenges of using EEG in veterinary clinical practice, non-EEG parameters could be a promising alternative to monitor seizures more objectively.